2022
DOI: 10.3390/nu14122536
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting: Potential Utility in the Treatment of Chronic Pain across the Clinical Spectrum

Abstract: Dietary behavior can have a consequential and wide-ranging influence on human health. Intermittent fasting, which involves intermittent restriction in energy intake, has been shown to have beneficial cellular, physiological, and system-wide effects in animal and human studies. Despite the potential utility in preventing, slowing, and reversing disease processes, the clinical application of intermittent fasting remains limited. The health benefits associated with the simple implementation of a 12 to 16 h fast s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 206 publications
(257 reference statements)
0
10
0
Order By: Relevance
“…Scores on the sensory subscale of the McGill Pain Questionnaire were the most notable change in pain. Intermittent fasting is believed to impact pain specifically through reduction in inflammatory cytokines and oxidative stress ( 32 ). It may also increase synaptic plasticity and aid in preservation of myelin ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores on the sensory subscale of the McGill Pain Questionnaire were the most notable change in pain. Intermittent fasting is believed to impact pain specifically through reduction in inflammatory cytokines and oxidative stress ( 32 ). It may also increase synaptic plasticity and aid in preservation of myelin ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent fasting is believed to impact pain specifically through reduction in inflammatory cytokines and oxidative stress ( 32 ). It may also increase synaptic plasticity and aid in preservation of myelin ( 32 , 33 ). Reductions in fatigue were most pronounced in the physical and psychosocial subscales of Modified Fatigue Impact Scale.…”
Section: Discussionmentioning
confidence: 99%
“…Our study highlighted that the change in pain tolerance was independent of mood. In addition, there was evidence of a beneficial effect of intermittent fasting on cognitive function ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…4.1 Nutritional strategies: Fasting, phytochemicals, phytomelatonin, and fermented food 4.1.1 Fasting Fasting is an effective way to recover mitochondrial efficiency, and multiple human studies have shown its ability to restore metabolic pathways in people suffering from chronic pathologies. Fasting regimens are promising primary and secondary prevention strategies in patients suffering from metabolic and cardiovascular diseases (Oliveira et al, 2022;Papakonstantinou et al, 2022;Vasim et al, 2022;Zang et al, 2022), pain, inflammation and immune conditions (Feng et al, 2022;Fitzgerald et al, 2022;Parveen and Alhazmi, 2022), cancer (Lv et al, 2014;Marinac et al, 2016;Taucher et al, 2022;Tiwari et al, 2022), and neurological diseases characterized by altered mood, sleep, pain, and cognition (Phillips, 2019;Brocchi et al, 2022;Caron et al, 2022;Feng et al, 2022;Lobo et al, 2022;Xu et al, 2022).…”
Section: Figurementioning
confidence: 99%